2021
DOI: 10.1088/1361-6595/ac0a46
|View full text |Cite
|
Sign up to set email alerts
|

Determination and control of ion parameters in complex plasma of a DC discharge

Abstract: Complex plasmas, comprising a low-pressure DC discharge plasma and charged microparticles, form traps that can accumulate and localize ions. A loss of ions and electrons always occurs on the surfaces of the microparticles, which can lead to a decrease in the ion and electron densities in the plasma bulk. However, in most cases, the collective effect of the interaction between the discharge plasma and the dust cloud leads to an increase in the ion density-both around and inside the dust cloud-in comparison with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…It was shown in experiments [50,51] and calculations [23,52] that microparticles immersed in plasmas should heat up from several K to several tens K with respect to the neutral gas due to the kinetic and potential energy, the electrons, ions and excited atoms deposit on their surfaces. On the other hand, QD photoluminescence is known to experience the red shift on the increase of the QD temperature [40,[53][54][55].…”
Section: Heating Of a Microparticle Surface In A Plasmamentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown in experiments [50,51] and calculations [23,52] that microparticles immersed in plasmas should heat up from several K to several tens K with respect to the neutral gas due to the kinetic and potential energy, the electrons, ions and excited atoms deposit on their surfaces. On the other hand, QD photoluminescence is known to experience the red shift on the increase of the QD temperature [40,[53][54][55].…”
Section: Heating Of a Microparticle Surface In A Plasmamentioning
confidence: 99%
“…A certain group of methods requires assumptions on the spatial distribution of plasma parameters [15,16] and/or rely on the exact values of plasma parameters [19]. Values of the plasma parameters are often taken from measurements in dust-free plasmas, whereas it has been shown that dust strongly affects the local values of plasma parameters as well as their global distributions [9,[20][21][22][23]. All the above-mentioned issues limit the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Charged particles bring their kinetic as well as potential energy to the plasma-facing surface, which is cooled by neutral gas as well as by thermal radiation. [29][30][31][32] Heating is, therefore, along with charging, an unavoidable consequence of the exposure of the surface to any ionized medium. The spectral shifts caused by these two phenomena have to be therefore distinguished.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments of [25] have shown that exposure of QDs to the fluxes of charged particles is connected not only with the surplus-charge-induced Stark shift, but also with the thermal shift of the photoluminescence spectrum [28][29][30]. Charged particles bring their kinetic as well as potential energy to the plasma-facing surface, which is cooled by neutral gas as well as by thermal radiation [31][32][33][34]. Heating is, therefore, along with charging, an unavoidable consequence of the exposure of the surface to almost any ionized medium.…”
Section: Introductionmentioning
confidence: 99%